2015
DOI: 10.5194/isprsarchives-xl-1-w4-207-2015
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Spectral Sensitivity Functions of Un-Modified and Modified Commercial Off-the-Shelf Digital Cameras to Enable Their Use as a Multispectral Imaging System for Uavs

Abstract: ABSTRACT:Commercial off-the-shelf (COTS) digital cameras on-board unmanned aerial vehicles (UAVs) have the potential to be used as multispectral imaging systems; however, their spectral sensitivity is usually unknown and needs to be either measured or estimated. This paper details a step by step methodology for identifying the spectral sensitivity of modified (to be response to near infra-red wavelengths) and un-modified COTS digital cameras, showing the results of its application for three different models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…We did not examine the response of our cameras employed. Berra et al [39] investigated the spectral sensitivity of several unmodified and one filter-modified camera, and found that all of the unmodified cameras showed similar ranges within the visible spectrum, with almost all of the RGB channels covering the range of 400-700 nm, but with varying degrees of sensitivity and substantial band overlap [39]. The filter-modified camera exhibited well-characterized sensitivities in the visible range that were narrower and of more equal intensities than those of the unmodified cameras.…”
Section: Camera Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…We did not examine the response of our cameras employed. Berra et al [39] investigated the spectral sensitivity of several unmodified and one filter-modified camera, and found that all of the unmodified cameras showed similar ranges within the visible spectrum, with almost all of the RGB channels covering the range of 400-700 nm, but with varying degrees of sensitivity and substantial band overlap [39]. The filter-modified camera exhibited well-characterized sensitivities in the visible range that were narrower and of more equal intensities than those of the unmodified cameras.…”
Section: Camera Sensitivitymentioning
confidence: 99%
“…The spectral sensitivity of the bands and wavelength transmittance of filters of most COTS cameras are unknown, unless exposed to monochromatic light [39]. We did not examine the response of our cameras employed.…”
Section: Camera Sensitivitymentioning
confidence: 99%
“…On image based analysis, Bayer filters in camera sensors have color overlaps, which would need to be removed to make measurements of specific light bands [19]. This means that in common cameras, RGB (Red, Green and Blue) channels represent broad and nonspecific sections of the light spectrum [20].…”
Section: Resultsmentioning
confidence: 99%
“…Light transmission values are presented in a standardized 0 to 1 scale. To overcome the limitations of a higher number of plant height values (20), as compared to a lower number of light transmission readings (17), the latest were taken randomly, without knowing the current height of the plants whose leaves were been assessed. …”
Section: Smartphone Based Measurements Of Light Transmission Through mentioning
confidence: 99%
“…However, the spectral response of consumer digital cameras is not provided by camera manufacturers. There are several methods for measuring and estimating the spectral response of a camera system including two standards for characterisation, one produced by the European Machine Vision Associations (EMVA (Berra et al, 2015;Bongiorno et al, 2013;MacDonald, 2015;Prasad and Brown, 2013). While there are several methods for measuring and estimating spectral response, a filter-based method used by MacDonald (2015) presented an accessible option that could include measurements into the NIR for a modified camera.…”
Section: Spectral Responsementioning
confidence: 99%